Factors associated with physicians’ perception of physician-patient relationship - Casanova Saldarriaga, Johnny Francisco (2017)
Objective: To determine the factors associated in the perception of physician-patient relationship by physicians who work at the Hospital Nacional Edgardo Rebagliati Martins, 2015. Materials and methods: An observational, prospective, cross-sectional, analytic, non-experimental study. The study population consisted of all the physicians who work at the Head and Neck Surgery Department, which includes the Otolaryngology (15 physicians), Ophthalmology (25 physicians), and Head and Neck (14 physicians) Specialty Areas. The research instrument was a self-administered survey based on three topics: 1) Influence of technology and specialization in dehumanizing physician-patient relationship. 2) Influence of judicialization of medicine. 3) Respect and confidence of patients. Eighteen questions based on the three main topics were asked, and physician’s sociodemographic, educational and cultural data were collected. The instrument was validated by a team of experts, at a confidence level of 0.92 (Cronbach’s Alpha score). Besides the survey, physicians underwent a personal interview, in order to find out their personal opinion about their physician-patient relationship. Data were analyzed using IBM SPSS Statistics statistical software. Statistical analysis was conducted using chi-square test, with a significance level of 5%. Results: The research assessed 30 specialty physicians with a mean age of 53.57 years: 83.3% of the interviewed physicians were male, 43% majored in ophthalmology, 36.7% were born in Lima, 43.3% finished high school at a public school, 66.7% studied medicine at a public university, 93.3% pursued major studies at a public university, 46.7% stated that their mother was born in the Peruvian highlands, 63.3% stated that their father was born in the Peruvian highlands, 87% were Catholics, 83% said that they chose to study medicine by vocation, 90% practiced medicine in the private sector, 43% volunteered in social support programs for low-income people, and 46.7% felt that there was a good physician-patient relationship. Conclusions: Technology and specialization do not contribute to dehumanization of physicians. Studying patients by organs often causes to miss the perception of the patient as a whole. Evidence-based medicine is only necessary as a complement to physician’s experiences. Bureaucratic processes and long waiting periods discourage the patient. It is important to assign more time to patients in the outpatient health care service. The perception of physician-patient relationship strongly correlates to the satisfaction of both patient and physician.